Multiscale Deformation of Commercial Titanium and Ti一6Al-4V Alloy Subjected to Electron Beam Surface Treatment; Physical Mesomechanics; Vol. 21, iss. 5 - Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Perevalova O. B. Olga Borisovna; Sinyakova E. A. Elena Aleksandrovna; Krukovsky K. V. Konstantin Vitaljevich; Martynov S. A. Sergey Andreevich (2018, 2018)
Title screen